Answer:
Explanation
Standard form
![y](https://img.qammunity.org/2021/formulas/mathematics/college/twf9i2c5fy0ini24wyx9lhqb3ajnch478u.png)
Hence your P(t) = -3, Q(t) = 2
![y(x) = Vy_1(x)\rightarrow y'(x) = V'y_1(x) + Vy_1'(x) ~~~and ~~~y](https://img.qammunity.org/2021/formulas/mathematics/college/tqpsaikxw0kufxaix1rxx6m7jx7tno0j3g.png)
After replacing all y", y' and y to homogeneous part, you will have
because
![e^x\\e 0](https://img.qammunity.org/2021/formulas/mathematics/college/f9709nupf4jztp73r2ile13wbjcrx0rut4.png)
Let U = V'
.
![lnu= -5x \rightarrow u = e^(-5x)](https://img.qammunity.org/2021/formulas/mathematics/college/tj2vkumew6prsa16040vqzzbr0ff82d6nc.png)
Replace back,
![V' = e^(-5x)\rightarrow V= (e^(-5x))/(-5)](https://img.qammunity.org/2021/formulas/mathematics/college/tn3vt9f744tx6pmc66xg9t8hwb5axbv461.png)
then
![y(x) = V y_1(x) = (e^(-4x))/(-5)](https://img.qammunity.org/2021/formulas/mathematics/college/5qg7c3yxqh626f2z3ne8h7wocsx3n1vcv2.png)
So, general solution of the ODE is
![Ay_1(x) + By_2(x)](https://img.qammunity.org/2021/formulas/mathematics/college/g7maol5bn245bgnj03h55bp1qlvrc2pm6z.png)
Particular solution is just take derivative of the general one twice and plug back into the original ODE to find A and B
You can finish it by yourself. Let me know if you need more help